Mutasi Terhadap Kinerja Karyawan Pada PT Kereta Api Indonesia (Persero) Daerah Operasi 1 Jakarta - Ferdian Erlangga Rosa (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
This study aims to determine the effect of the mutation on the performance of employees at PT Kereta Api Indonesia (Persero) Regional Operations 1 Jakarta. In this study using survey methods and eksplansi with the collection directly from the original source, in the form of questionnaires were drawn from a sample. The sample in this study were all employees of PT Kereta Api Indonesia (Persero) Jakarta Regional Operations 1 102 respondents. Data analysis and processing techniques used are validity, reliability test, descriptive analysis, simple linear regression analysis. Based on the results of data processing test